Effect of Acupuncture Cooperated with Low-frequency Repetitive Transcranial Magnetic Stimulation on Chronic Insomnia: A Randomized Clinical Trial - Zhang, Yang-pu; Liao, Wei-jing; Xia, Wen-guang (Current medical science, 2018)
Summary The effect of acupuncture cooperated with low-frequency repetitive transcranial magnetic stimulation (rTMS) on chronic insomnia was explored. Seventy-eight patients with chronic insomnia were randomly allocated into two groups: treatment group and control group. In the treatment group, the patients received acupuncture combined with rTMS treatment, and those in the control group were given acupuncture cooperated with sham rTMS treatment, 3 days per week for 4 weeks. Before and after treatment, the primary outcomes including the scores on Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI) and the secondary outcomes including total sleep time (TST), sleep onset latency (SOL), wake after sleep onset (WASO), sleep efficiency (SE%) recorded by sleeping diary and actigraphy were observed in both groups. Seventy-five participants finished the study (38 in treatment group and 37 in control group respectively). After treatment, the scores in the two groups were improved significantly, more significantly in the treatment group than in the control group. It can be inferred that acupuncture cooperated with rTMS can effectively improve sleep quality, enhance the quality of life of patients and has less side effects